"Practical reason is not the will": Kant and Reinhold's dilemma. (19th March 2019) - Noller, Jörg
Abstract: Contrary to Karl Leonhard Reinhold's theoretical critique of Kant's philosophy, his practical critique has been almost unknown. In my paper, I shall reconstruct Reinhold's practical philosophy after Kant. I will concentrate on the so‐called Reinhold's dilemma, which concerns the problem of moral imputability in the case of immoral actions in Kant. Also, I shall explain how Reinhold tried to escape this dilemma by introducing a new action theory and by sharply distinguishing between reason and will. Finally, I shall evaluate Reinhold's practical significance by relating his conception of individual freedom to recent theories of volitional self‐determination.